LINGUISTIC SEXISM IN CURRENT UPPER SECONDARY SCHOOL ENGLISH LANGUAGE TEXTBOOKS: TIẾNG ANH 10, TIẾNG ANH 11 AND TIẾNG ANH 12 - Canh, Nguyen Doan (VNU Journal of Foreign Studies, 2017)
This article reports my study on linguistic sexism in current Vietnamese upper secondary school English language textbooks: Tiếng Anh 10 , Tiếng Anh 11 and Tiếng Anh 12 . The study was aimed at finding out how often linguistic sexism occurs in these textbooks and uncovering the hidden messages conveyed through this linguistic sexism. The results of the study showed that linguistic sexism occurs rather often in the three English textbooks and through it the messages of women’s low status are conveyed.